2014
DOI: 10.1099/ijs.0.058610-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus ligniniphilus sp. nov., an alkaliphilic and halotolerant bacterium isolated from sediments of the South China Sea

Abstract: An alkaliphilic and halotolerant Gram-stain-positive bacterium, which was isolated from sediment samples from the South China Sea, was subjected to a taxonomic study. The isolate, strain L1 T , grew well at a wide range of temperatures and pH values, 10.0-45.0 6C and pH 6-11, with optima at 30 6C and pH 9.0, respectively. The growth of strain L1 T occurred at total salt concentrations of 0-10 % (w/v) with an optimum at 2 % (w/v). Phylogenetic analysis based on 16S rRNA sequence comparison indicated that the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…Accordingly, this isolate could be fit for the treatment of mixed waste containing fish and seaweed. Some Bacillus strains possessing tolerance within a range of NaCl concentrations have been reported: Bacillus flexus (3.5-10%; Trivedi et al, 2011), Bacillus megaterium (4-12%; Mishra et al, 2011), B. licheniformis (7-12%; Ghani et al, 2013), and Bacillus ligniniphilus (0-10%; Zhu et al, 2014). It was also reported that a Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this isolate could be fit for the treatment of mixed waste containing fish and seaweed. Some Bacillus strains possessing tolerance within a range of NaCl concentrations have been reported: Bacillus flexus (3.5-10%; Trivedi et al, 2011), Bacillus megaterium (4-12%; Mishra et al, 2011), B. licheniformis (7-12%; Ghani et al, 2013), and Bacillus ligniniphilus (0-10%; Zhu et al, 2014). It was also reported that a Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Most members have MK-7 as the major respiratory quinone; iso-C 15:0 and anteiso-C 15:0 as the major fatty acids; and meso-diaminopimelic acid as the diagnostic diamino acid in the peptidoglycan. Bacillus species have been isolated from various habitats, including air (Shivaji et al 2006), ancient tombs (Gatson et al 2006), brown alga (Ivanova et al 2004), desert sands , forest soils (Chen et al 2011), freshwater (Baik et al 2010), ginseng root (Qiu et al 2009), hot springs (Nazina et al 2004), marine sediments (You et al 2013;Zhu et al 2014), sea water (Yoon et al 2003), sandy soil (Lee et al 2008) and a soda lake (Reddy et al 2015). Many can be found in saline habitats (Amoozegar et al 2009;Arahal et al 1999;Lee et al 2006;Lim et al 2006;Pappa et al 2010;Shi et al 2011;Xue et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with physical and chemical methods, microbial lignocellulosic degradation is a green process [8]. Bacillus is generally an excellent degrader, with specific strains exhibiting various abilities for lignocellulose degradation, including the degradation of cellulose, hemicellulose, and lignin [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%